Synthesis of Some Novel Benzimidazole Derivatives as Anticancer Agent and Evaluation for CDK2 Inhibition Activity - El-Hameed, Rania H. A.; Fatahala, Samar S.; Sayed, Amira Ibrahim (Medicinal Chemistry, 2022)
Background: Thiobezimidazoles reveal various pharmacological activities due to similarities with many natural and synthetic molecules; they can easily interact with biomolecules of living systems. Objective: A series of substituted 2-thiobezimidazoles have been synthesized. Twelve final compounds were screened for in vitro anti-cancer activities against sixty different cell lines. Methods: The spectral data of the synthesized compounds were characterized. A docking study for active anticancer compounds and CDK2/CyclinA2 Kinase assay against standard reference; Imatinib, were performed. Results: Two compounds (3c&3l) from the examined series revealed effective antitumor activity in vitro against two-cancer cell lines (Colon Cancer (HCT-116) and Renal Cancer (TK-10). The docking study of synthesized molecules discovered a requisite binding pose in the CDK-ATP binding pocket .3c &3l were promoted in the CDK2/CyclinA2 Kinase assay against standard reference Imatinib. Conclusion: Against all tested compounds; two compounds 3c &3l were found active against two types of cell-lines.
Keywords: Synthesis